Forest of secrets - Hunter, Erin. (New York : HarperCollins, 2003)
The warrior cat Fireheart's determination to uncover the truth about another warrior's death leads him deep into danger, and reveals secrets that test the strength of clan loyalties.
Keywords: Cats; Fantasy